Insights into the thermal conductivity of MOF-5 from first principles. Issue 58 (17th November 2021) - Zhang, Shenglong; Liu, Jian; Liu, Linhua
Abstract : The mechanism of thermal transport in MOF-5 and the tailoring strategies of thermal conductivity κ via metal substitution and strain engineering were investigated by first-principles calculations. Abstract : Metal–organic frameworks (MOFs) have been extensively studied in many fields due to their abundant porous structures. The mechanism underlying the thermal conduction properties of MOFs, which plays an essential role in a wide variety of applications such as adsorbents and thermoelectric devices, remains elusive. It is also highly desirable to achieve the efficient modulation of thermal conductivity in MOFs via experimentally accessible methods such as metal substitution and strain engineering. In this work, we perform first-principles calculations to investigate the thermal transport properties of MOF-5, a representative prototype of MOFs. We find an ultralow thermal conductivity ( κ ) of 0.33 W m −1 K −1 at room temperature, in excellent agreement with the experimental measurement. Such ultralow κ is attributed to the strong phonon–phonon scattering that arises from the dense and intertwined low-frequency phonons. The phonon dispersion leads to unusual tuning strategies of κ, since conventional designing guidelines ( e.g. substitution of heavier atoms or application of tensile strain is preferred in pursuit of lower thermal conductivity) are not fully obeyed in MOF-5. We find that isovalent substitutions of Zn atoms with (lighter) Mg and (heavier) Cd atoms both result in significant reduction of κ, due to the enhanced phonon scattering rates that are associated with the stronger bond strength and the larger atomic mass, respectively. We further demonstrate that the so-called "guitar string" vibrations are responsible for the anomalous non-monotonic variation of κ in MOF-5 under tensile strain. This work provides fundamental insights into the thermal transport mechanisms in MOF-5, which may have some important implications for the thermal management applications utilizing MOFs.